2022
DOI: 10.3390/en15186661
|View full text |Cite
|
Sign up to set email alerts
|

Study on Aerodynamic Characteristics of a Savonius Wind Turbine with a Modified Blade

Abstract: In order to improve the static start-up problem of Savonius wind turbines, a Savonius wind turbine with a modified blade is proposed. It was obtained by twisting the half-cylindrical blades of the basic Savonius wind turbine by 70°. The aerodynamic performance of the wind turbine before and after the modification was compared. Firstly, the static torque coefficient of two wind turbines at different azimuth angles were obtained by means of three-dimensional numerical simulation. The static flow field around the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…Ushiyama [28] carried out numerical investigations on the start-up and steady performance of several drag-based rotor configurations. It has been reported that as the rotor's aspect ratio increases, the rotor reaches its steady performance earlier, which is in-line with the observations of Mu et al [27]. Evaluating the effects of overlap ratio, it has been reported that increase in overlap is reflected in slightly higher steady operational speed of the rotor.…”
Section: Drag-based Rotorssupporting
confidence: 85%
See 3 more Smart Citations
“…Ushiyama [28] carried out numerical investigations on the start-up and steady performance of several drag-based rotor configurations. It has been reported that as the rotor's aspect ratio increases, the rotor reaches its steady performance earlier, which is in-line with the observations of Mu et al [27]. Evaluating the effects of overlap ratio, it has been reported that increase in overlap is reflected in slightly higher steady operational speed of the rotor.…”
Section: Drag-based Rotorssupporting
confidence: 85%
“…Start-up failure was recorded at AoAs of 70° and 150°, providing insights into the dead band range of AoAs. Similar to the dead band range of AoAs observed by Mu et al [27], the initial acceleration of the rotor is shortly followed by deceleration until a slight reverse rotation is noticed. The rotor demonstrates repetition of both these stages in the dead band range, showing a sinusoidal pattern in the rotational speed of the rotor.…”
Section: Drag-based Rotorssupporting
confidence: 82%
See 2 more Smart Citations
“…The comparison of the percentage increase in the improved power coefficient obtained with this study with other studies in the literature is given in Table 1. It is possible to classify the literature studies on this subject as additional designs made outside of [26] and structural designs made inside of Savonius wind turbines [27,28]. Here, additional guide design studies made in front of or around the turbine without any modifications to the conventional Savonius wind turbines with two semi-circular blades were evaluated.…”
Section: Discussionmentioning
confidence: 99%